The Abundance and Distribution Pattern of Echinoderms in Intertidal Zone between Sadranan and Slili Beach, Gunung Kidul, Yogyakarta: Abundance and Distribution Pattern of Echinoderms in Intertidal Zone between Sadranan and Slili Beach, Gunung Kidul, Yogyakarta - Farhan Wali Bachtier; Fania Baeta Roska Khalallia; Herin Yoga Lesti; Naila Nabila Rahmani; Ni Made Sri Winasti; Syifa Evilia Maharani; Nadia Andilala; Rury Eprilurahman (FKIP, Universitas Palangka Raya, 2021)
Echinoderm is one of the phylum which has high diversity and abundance in Indonesia, especially in Gunung Kidul, Yogyakarta. Sadranan and Slili beach are side by side beach located in Gunung Kidul. This beach is dominated by coral and rocky coral with macroalgae that provide the habitat of Echinoderms. This research is conducted to study the abundance and distribution pattern of Echinoderms in the intertidal zone between Sadranan and Slili beach. Sampling was carried out on Friday, 4 October 2019 at 05.00 p.m. in the intertidal zone using quadrat plot methods. The beach area is 2240 m2 which is divided into 21 plots with 1 x 1 m size. Data analysis was performed by measuring Margalef index (D), Pielou index (e), and Shannon-Wiener index (H’) then analyzing the distribution pattern and habitat parameters. The result shows that the Echinoderms which has the highest abundance is Echinometra mathei with 19 individual founds. The distribution pattern of Echinometra mathei, Stomopneustes variolaris, Heterocentrotus trigonarius, Ophiocoma erinaceus, Macrophiotrix longipeda, Ophiomastix annulosa, and Echinus sp. is clumped. The distribution pattern of Tripneustes gratilla, Diadema antillarum, Echinotrix calamaris, and Ophiocoma scolopendrina is uniform